find the antiderivative of x^2e^(3x)

- Martingale
**Posts:**333**Joined:**Mon Mar 30, 2009 1:30 pm**Location:**USA-
**Contact:**

use integration by partsfind the antiderivative of x^2e^(3x)

i get ((x^2e^3x)/3)-((2xe^3x)/9)-((2e^3x)/9)+C

- Martingale
**Posts:**333**Joined:**Mon Mar 30, 2009 1:30 pm**Location:**USA-
**Contact:**

close...i get ((x^2e^3x)/3)-((2xe^3x)/9)-((2e^3x)/9)+C

look at the last bit...(2e^3x)/9

would it be e^(3x)/3?

- Martingale
**Posts:**333**Joined:**Mon Mar 30, 2009 1:30 pm**Location:**USA-
**Contact:**

nowould it be e^(3x)/3?

- Martingale
**Posts:**333**Joined:**Mon Mar 30, 2009 1:30 pm**Location:**USA-
**Contact:**

find the antiderivative of x^2e^(3x)

I'll do it step by step

udv=(x^2)(e^3x/3)-(e^3x/3)(2xdx)

=(x^2e^3x)/3-(2xe^3x)dx/3)

Then do I need to find the antiderivative of the second part (2xe^3x)dx/3) because there are two fnc (2x/3) and (e^3x)

u= 2x/3 dv= (e^3x)dx

du= (2/3)dx v= (e^3x/3)

am I going in the right direction?

udv=(x^2)(e^3x/3)-(e^3x/3)(2xdx)

=(x^2e^3x)/3-(2xe^3x)dx/3)

Then do I need to find the antiderivative of the second part (2xe^3x)dx/3) because there are two fnc (2x/3) and (e^3x)

u= 2x/3 dv= (e^3x)dx

du= (2/3)dx v= (e^3x/3)

am I going in the right direction?

- Martingale
**Posts:**333**Joined:**Mon Mar 30, 2009 1:30 pm**Location:**USA-
**Contact:**

yesI'll do it step by step

udv=(x^2)(e^3x/3)-(e^3x/3)(2xdx)

=(x^2e^3x)/3-(2xe^3x)dx/3)

Then do I need to find the antiderivative of the second part (2xe^3x)dx/3) because there are two fnc (2x/3) and (e^3x)

u= 2x/3 dv= (e^3x)dx

du= (2/3)dx v= (e^3x/3)

am I going in the right direction?

for the antiderivative of the second part then I would get

(2x/3)(e^3x/3)-(e^3x/3)((2/3)dx)

(2x/3)(e^3x/3)-(e^3x/3)((2/3)dx)